Protection of low rectal anastomosis with a new tube ileostomy using a biofragmentable anastomosis ring: A retrospective study. Issue 45 (November 2016) - Liu, Liming; Huang, Qi; Wang, Jialiang; Chen, Quanning; Lin, Rui; Ge, Bujun
Abstract : Abstract: A temporarily defunctioning stoma, while effective at reducing symptomatic anastomotic leakage after low anterior resection (LAR) of rectal cancer, and its subsequent closure, is associated with significant morbidity. Here, we devised a new tube ileostomy using a biofragmentable anastomosis ring (TIB) with no need for reversal. This is a retrospective cohort study. From June 2011 to March 2015, TIBs were performed on 31 consecutive patients with mid- or low-rectal cancer who underwent elective laparoscopic LARs. From January 2008 to May 2011, 25 similarly diseased patients underwent elective laparoscopic LARs and conventional loop ileostomy (LI) and were included as controls. All of the anastomotic sites were within 6 cm of the anal verge. Demographic, clinical feature, and operative data were recorded. The demographic features of both groups were similar. The TIB mean surgical duration was significantly lower than in the LI group (215 ± 28 vs 245 ± 54 min, P = 0.010). Because of readmission for stoma closure, the total hospital stay of the LI group was longer than that of the TIB group (38.1 ± 26.5 vs 19.1 ± 7.9 days, respectively, P = 0.002). Ileal content was completely diverted by TIB for 13.7 ± 2.1 (range, 10–19) days postoperatively. The drainage tube was removed on postoperative day 27.8 ± 6.9 (range, 20–44), and the mean continued duration of the discharge tract, before fistula healing, was 4.5 ± 1.9 (range, 2–10) days. Postoperative complications of the 2 modalities were not significant. In the TIB group, 1 rectovaginal fistula occurred 30 days postsurgery. In the LI group, 1 rectovaginal fistula occurred 3 months after stoma closure. Both complications were treated with transverse colostomy. No major TIB associated complications were observed in the present study. TIB is a safe, feasible, effective, but time-limited diversion technique, which may reduce symptomatic anastomosis leakage after LAR for rectal cancer.